Mending the Safety Net through Source of Income Protections: The Nexus between Antidiscrimination and Social Welfare Law - Flagg, Kinara (Columbia Journal of Gender and Law, 2011)
Nina is an African American woman and a single mother with five children living in New York City.’ One of her children is severely disabled. Last year, after a long wait, Nina became eligible for a housing voucher through the federal Housing Choice Voucher Program (also known as Section 8). In spite of the promise of rental assistance, Nina and her family have repeatedly been denied housing. The landlords and real estate agents that sent her away never mentioned her race, the fact that she has children, or that one of her daughters is disabled. If they had, Nina would have a clear legal claim under the Fair Housing Act (FHA or “the Act”). Instead, landlords and agents continue to deny Nina housing on account of her housing voucher, claiming that the property owner cannot or does not accept those types of vouchers and that the owner will only accept people with “real jobs” as tenants. This treatment may not seem as egregious as having a door slammed in one’s face on account of one’s race or being told by a real estate agent that there are more “people like her” nearby in a different neighborhood. However, Nina and her children are being discriminated against, and Nina’s ability to choose where to live has been interfered with and frustrated. What Nina and her family have experienced, and what many others like her experience each day, is known as source of income discrimination (SOI discrimination). In spite of the fact that her income is lawfully obtained through a federal voucher program that has operated since the 1970s, landlords and real estate agents fail to make rental units available to prospective tenants like Nina because of how she plans to pay her rent. The FHA protects against discrimination on the basis of race, color, national origin, religion, sex, familial status and disability in the sale or rental of properties. However, it does not include a protection against SO discrimination, discrimination that is often conducted so openly that it may be difficult to view it at first as a form of discrimination, but like other forms of discrimination, SO discrimination is a significant obstacle to minorities and people with disabilities searching for housing. While landlords may openly refuse prospective tenants based on their status as voucher holders or recipients of public assistance, denial in such cases maybe a thinly veiled means of rejecting tenants on the basis of race, familial status or disability.